English: English - Junaidi, Sahrul Arifin; Abdul Hakim; Ibnu Arabi (Jurnal Ilmiah Ilmu Ushuluddin, 2024)
This article discusses Sufitic values in a tradition that exists in the Madurese community in Mekar Sari Village, Kintap District, Tanah Laut Regency. This tradition is called Koloman, which is an Islamic-based tradition that is carried out every Thursday Night in turns and moving from one member's house to another. The Koloman tradition contains many sufistic values in every detail of its implementation. The purpose of this research is to find out how the Koloman traditions of the Madurese community in Mekar Sari Village is like and what the sufistic values are in the Koloman traditions of the Madurese community there. This research uses a qualitative field research method through a descriptive approach which aims to describe a phenomenon in detail. The data collection techniques used are observation, interviews, and documentation. The data obtained was then analyzed using general theories of value and tashâwwuf. Based on the results of research that has been carried out, it can be concluded that the Koloman tradition in Mekar Sari Village is a gathering activity of the Madurese tribe every Friday night which is filled by men with the practice of istighâsah, khususan, Yasin, tahlil, and prayers given to the ancestors or family members who have died, this is done by moving to each house in the community that is part of Koloman. From every detail of its implementation, the researcher can trace the existence of sufistic values in the Koloman tradition which are expressed through zhâhiriyyah and bâthiniyyah obedience. Sufistic values in zhâhiriyyah obedience include ath-taubah, Amr ma'rûf wa nahî munkâr, al-ikhtilât, dikr Allâh, dikr al-maût, and the etiquette of visiting and receiving guests. The Sufistic values in bâthiniyyah obedience include gratitude, generosity, sincere, rahmah, and istiqâmah